Sindicatos, trabajadores y lucha de clases en el marco del Pacto Social. Análisis de tensiones y disputas en la fábrica Yelmo - Mariana Stoler (Nuevo mundo - Mundos Nuevos, 2021)
In 1973, in Argentina, the return of democracy was marked by the attempts to strengthen the State against civil society, rehabilitating the political sphere as a place to settle social conflicts. The Pacto Social, the chosen tool for containing the intersectoral conflicts for income distribution, sought to rehabilitate legitimate political actors – such as unions – that could contain the class struggle. In the previous years, however, opposition to traditional Peronist union leaderships had been developed in factories and at all levels of the organization. The union became one of the places where social tension was manifested. The emergence of new political identities and new collective actors that claimed and re-signified the image of the first Peronism generated internal disputes within the Peronist Movement that intensified the social tension.However, the growing opposition among the rank-and-file was heterogeneous and did not manage to mobilize all the workers: the workers' organization in the factories was “crossed” by different contradictions. In this paper, we will analyze how these different elements interacted in the conflict at the Yelmo factory in La Matanza, during the second half of the year.